Foreign Patient’s Satisfaction from Hospitality Services–Medical Tourism at JCI Accredited Hospitals of Delhi-NCR, India - Shukla, Rajnish; Singh, Malini; Saxena, Sanjeev Kr. (International Journal of Psychosocial Rehabilitation, 2020)
This study is done to understand the scope of the hospitality services provided to foreign patients admitted at JCI accredited hospitals at Delhi-NCR. This study evaluates the satisfaction of foreign patients from hospitality services provided to them at these hospitals. A review of existing literature and focus group discussions were conducted to explore the scope of hospitality services and facilities offered to foreign patients coming to these hospitals. Primary data through questionnaire was collected and statistically analysed to get some meaningful insights about the patient satisfaction from these services. Study finds that JCI accredited hospitals at Delhi NCR deliver considerably good patient’s care and pay attention to hospitality style non clinical services to foreign patients. These hospitals consider hospitality services as an opportunity to bring brand excellence and also use it as a differentiator for better patient satisfaction. However this study found some neglected areas of services offered and some unattended needs and desires of the foreign patients. Study explores the foreign patient satisfaction from such services and findings are going to be valuable to the hospitals trying to do their best in achieving higher patient satisfaction. The study offers a first-hand review of hospitality services and its elements in Internationally Accredited Hospitals at Delhi NCR. Hospitals dealing with foreign patients and targeting to benefit from the growing scope of medical tourism where the patient’s expectations from non-clinical services are higher are going to benefit at large.